A new blind identification method for DS-CDMA systems with antenna array under multipath fading. - Xiang Yu (IEEE Journal on selected areas in communications)
In recent years, some blind adaptive multiuser detectors have been presented to implement multiuser detection with only the knowledge of the desired user's spreading code and propagation delay. We find, in this paper, that with the aid of the antenna array, multiuser detection can be achieved even without the desired user's spreading code and propagation delay, provided that the direction of arrival of every user is different from each other. Propagation delay and array response estimation methods are also proposed in this paper